EFFECT OF EASE OF USE OF THE APPLICATION, PERCEPTION SECURITY AND SHOPPING EXPERIENCE ON INTEREST TO REPURCHASE ON THE SHOPEE APPLICATION , CASE STUDY ON STUDENT OF THE FACULTY OF ECONOMICS AND BUSINESS UNIVERSITAS KRISTEN INDONESIA - Teresa Dortua Hutauruk; Sautman Sinaga; Emerald G. M Tobing (Universitas Kristen Indonesia, 2024)
This study means to survey the effect of the usability of the Shopee application, saw security, and shopping experience on the goal to repurchase inside the Shopee application. The exploration utilizes a quantitative methodology, using an internet based poll made with Google Structures. A purposive testing procedure was used, including 100 respondents who are FEB understudies at the Universitas Kristen Indonesia and are customary clients of the Shopee application. The examination information was dissected through expressive measurable tests, old style supposition tests, various direct relapse investigation, t-tests, F-tests, and the cefficient of asurance. The consequences of the different direct relapse investigation yield the condition Y = 0.572 + 0.17 X1 + 0.256 X2 + 1.034 X3 + e, with a coefficient of assurance of 0.718. The t-test results for the Usability variable (X1) show an importance worth of 0.001 (p < 0.05), for the View of Safety variable (X2) the importance esteem is 0.001 (p < 0.05), and for the Shopping Experience variabIe (X3) the importance esteem is 0.001 (p < 0.05). The F-test creates an importance worth of 0.001 (p < 0.05). That's what the review presumes: 1) Usability fundamentally and decidedly impacts repurchase goal, 2) Saw security essentially and emphatically impacts repurchase aim, 3) Shopping experience essentially and decidedly impacts repurchase expectation, and 4) Convenience, Saw Security, and Shopping Experience together altogether affect repurchase aim. Keywords: Ease of use, perceived security, shopping experience, repurchase intention